Investigation of Flow Characteristics in Valveless Piezoelectric Pumps with Airfoil Baffles at Varying Angles of Attack - Jun Huang; Hiba Affane; Bo Zhang; Ming Kuang; Jian Xiong; Siyao Zhang (Applied Sciences)
To investigate the impact of airfoil angle of attack on the output performance of a valveless piezoelectric pump with airfoil baffles, this study conducted comprehensive performance tests and full-flow field simulations of piezoelectric pumps across a range of angles. At a driving voltage of 100 V and with a Clark Y airfoil set at an angle of 0°, the piezoelectric pump reached a peak output flow rate of 200.7 mL/min. An increase in the angle of attack corresponded to a decline in both the maximum output flow rate and the maximum back pressure of the pump. Flow field simulation results demonstrated that an increased airfoil angle of attack led to a gradual increase in entropy production within the piezoelectric pump. Turbulent dissipation and wall entropy production were found to be more pronounced compared to viscous entropy production. High turbulent dissipation was primarily observed at the pump chamber inlet, the trailing edges of the airfoils in both the inlet and outlet pipes, and the outlet bend. As the angle of attack increased, the complexity of the vortex core structures within the flow field escalated as well. Regions with significant wall entropy production were notably concentrated at the outlet bend.